The thermal decomposition and combustion of building and finishing materials; Journal of Analytical and Applied Pyrolysis; Vol. 173 - Kuznetsov G. V. Geny Vladimirovich; Kropotova S. S. Svetlana Sergeevna; Kopylov N. P. Nikolay Petrovich; Novikova V. I. Viktoriya Ivanovna; Sushkina E. Yu. Elena Yurjevna; Strizhak P. A. Pavel Alexandrovich; Yashin V. V. Vadim Vladimirovich (2023, 2023)
Title screen